Robotic ileal ureter replacement for panureteral stricture disease: a step-by-step guide - Emily Ji; Devin Boehm; Jonathan Rosenfeld; Rebecca Arteaga; Jaewoo Kim; Aidan Raikar; Ziho Lee (Urology Video Journal)
Objective: Traditionally, open ileal ureter replacement (IUR) was a reconstructive option for patients with long-segment ureteral strictures not amenable to excision and primary anastomosis. The paradigm has shifted to favoring robotic substitution ureteroplasty using buccal mucosa graft and/or appendix to manage most long-segment strictures. However, for panureteral strictures, IUR remains an important tool in the reconstructive urologist's armamentarium. In this article, we describe our step-by-step approach for intracorporeal robotic right and left IUR and highlight key aspects of our surgical technique. Methods and Surgical Procedure: Our technique involves five major steps: proximal ureteral dissection, bowel harvest, bladder dissection, distal anastomosis, and proximal anastomosis. Given the need to optimize access to the upper and lower urinary tracts, we use two separate patient positions and port placement setups. The modified flank position is used to access the upper urinary tracts and the modified supine position is used to access the lower urinary tracts. Rotating the bed allows for toggling between the modified flank and modified supine positions without the need to reposition or re-drape the patient. For right sided cases, we prefer to orient the ileal ureter in an anti-peristaltic fashion to retroperitonealize the ileal ureter and optimize its mesenteric orientation. For left sided cases, the proximal portion or the entirety of the ileal ureter may be tunneled through the sigmoid mesentery. We prefer the latter option in patients with a history of stone disease to facilitate endoscopic access to the kidney. Postoperatively, we obtain a cystogram at two weeks and remove the urethral catheter if the cystogram is negative for urine leak. The stent is typically removed six weeks postoperatively. Our preference is to monitor for stricture recurrence with serial renal scans obtained three months, 12 months, and yearly thereafter. In cases where there is concern for stricture recurrence, the patients are taken to the operating room for an endoscopic evaluation. Results: Between 2/2022–7/2024, 8 patients underwent robotic IUR for panureteral stricture disease. The median age was 63 years (IQR 60–68), body mass index was 25 kg/m2 (IQR 22–27), and length of ureteral defect was 17 cm (IQR 15–21). The median operative time was 305 min (IQR 274–356) and estimated blood loss was 100 cc (IQR 100–200). There were no intraoperative complications. One patient (12.5 %) had a major (Clavien ≥ III) 30-day complication. This patient underwent concomitant robotic colorectal surgery for diverticulitis and developed an intra-abdominal abscess at the colonic anastomosis requiring drain placement. Median length of stay was 5 days (IQR 4–6). Table 1 lists preoperative and postoperative imaging findings for each patient. At a median follow-up of 20 months (IQR 12–22), all patients were surgically successful (no radiographic or clinical evidence of obstruction). No patients developed electrolyte abnormalities from urine reabsorption that required medical treatment (Table 1).Table 1 Pre and postoperative imaging findings.Table 1PatientEtiologyLaterality, severityPreoperative ImagingPostoperative imagingPre/Post creatinineF/u (mo)1Iatrogenic, stone surgeryL, 7 cm obliterated proximalCT mild L hydro with PCN, Renal scan 47 % functionRenal scan (28mo PO), no obstruction, mild hydro (54 % function)1.54/1.47282Iatrogenic, stone surgeryL, obliterated panureteralCT no hydro with PCNRenal scan (20mo PO), no obstruction, no hydro, (39 % function)0.7/0.8203Iatrogenic, stone surgeryR, obliterated panureteralCT no hydro with PCNRBUS (27mo PO), moderate R hydro, endoscopic evaluation without obstruction2.04/1.90274TraumaR, obliterated panureteralCT no hydro with PCN, 35 % functionCT (20mo PO), no hydro0.74/0.84205Iatrogenic, stone surgeryL, 11 cm obliteratedCT severe L hydroRBUS (18mo PO), no hydro1.78/1.85206Iatrogenic/malignant, UTUCR, failed prior Boari with urinary extravasationCT moderate R hydroRBUS (13mo PO) no hydro, Renal scan no obstruction (67 % function), cancer recurrence in contralateral kidney1.45/2.16157Iatrogenic, stone surgeryR, complete ureteral avulsionCT moderate R hydro with PCNCT (4mo PO) stable R hydro, no obstruction on endoscopic evaluation0.69/0.6148Iatrogenic, stone surgery failed prior repairL, 14 cm narrowingCT moderate L hydro with ureteral stentCT (3mo PO) improved L hydro, Renal scan no obstruction, 82 % function (found to have obstructing stone in contralateral kidney)0.99/1.393UTUC = upper tract urothelial carcinoma, L = left, R = right, cm=centimeters, PO = postoperative, PCN = percutaneous nephrostomy, hydro=hydronephrosis, CT = computed tompgraphy, mo= months, RBUS = renal bladder ultrasound. Conclusions: Intracorporeal robotic IUR is a challenging but effective surgery for management of long segment ureteral strictures. Simplifying robotic IUR into five reproducible steps may facilitate adoption of our technique.